2017
DOI: 10.1002/we.2092
|View full text |Cite
|
Sign up to set email alerts
|

Downwind pre‐aligned rotors for extreme‐scale wind turbines

Abstract: Downwind force angles are small for current turbines systems (1–5 MW) such that they may be readily accommodated by conventional upwind configurations. However, analysis indicates that extreme‐scale systems (10–20 MW) will have larger angles that may benefit from downwind‐aligned configurations. To examine potential rotor mass reduction, the pre‐alignment concept was investigated a two‐bladed configuration by keeping the structural and aerodynamic characteristics of each blade fixed (to avoids a complete blade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 28 publications
(52 reference statements)
3
52
0
Order By: Relevance
“…Wind turbine blade mass typically scales with R 2.2 , which is consistent with the 13.2‐MW turbine designed by Sandia National Labs . However, at extreme‐scale, the downwind thrust forces are no longer small relative to centrifugal forces.…”
Section: Extreme‐scale Load‐aligned Wind Turbinessupporting
confidence: 59%
See 2 more Smart Citations
“…Wind turbine blade mass typically scales with R 2.2 , which is consistent with the 13.2‐MW turbine designed by Sandia National Labs . However, at extreme‐scale, the downwind thrust forces are no longer small relative to centrifugal forces.…”
Section: Extreme‐scale Load‐aligned Wind Turbinessupporting
confidence: 59%
“…Wind turbine size (rotor diameter and hub height) is a primary factor determining a wind turbine's energy production. Larger turbines have larger swept areas and reach higher into the atmosphere, accessing stronger, and more consistent winds due to reduced effect of the boundary layer, which can increase their net power . This has led many to view extreme‐scale wind turbines (rated power exceeding 10 MW) as an effective way to lower levelized cost of energy (LCOE).…”
Section: Extreme‐scale Load‐aligned Wind Turbinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another concept to reduce mass-scaling issues is a highly coned, downwind rotor, which has shown that blade loads can be reduced by converting large cantilever loads at the blade root into tensile loads along the span of the blade (Ichter et al, 2016;Loth et al, 2017b). We will analyze this concept and its effect on the structural loading of the other wind turbine components besides the blades.…”
Section: Introduction 15mentioning
confidence: 99%
“…Innovations that can reduce loads can allow for larger turbines, which generate more power and still allow for a decreased cost of wind energy. One such innovation is the downwind load‐aligned wind turbine . Downwind indicates the rotor is positioned downstream of the tower.…”
Section: Introductionmentioning
confidence: 99%